Determinants of Poverty in Central Java Province 2013-2018 - Lilik Andrietya, Achyarnis; Pujiati, Amin; Setyadharma, Andryan (Journal of Economic Education, 2020)
This study aimed to assess whether there is influence between HDI, GRDP, Unemployment, Investment and Dummy (mainstay and not mainstay areas) on Poverty in Central Java. Based on data from BPS, poverty in Central Java Province in 2013-2018 are in number 2 after DI Yogyakarta in Java. This research use panel data with a Fixed Effect Model (FEM) approach. Sources of data obtained from the Central Statistics Agency and the Directorate General of Indonesian Financial Balance. The results showed that the variable HDI, GRDP and investment had a negative and significant effect on poverty in Central Java Province. While the Unemployment and Dummy variables (mainstay and non-mainstay areas) have a negative and not significant effect on poverty in Central Java Province. Simultaneously, shows that the overall independent variable can show its effect on poverty. The coefficient of determination R2 of 0.9899 which means 98.99 percent of poverty can be explained by the independent variable. While the remaining 1.01 percent is explained by variables outside the model.